Diffusion combustion of liquid heptane in a small tube with and without heat recirculating - Li, Junwei (2013)
In order to understand diffusion flame characteristics in a small tube, combustion of liquid n-heptane and air was experimentally and numerically studied. A tube of ID 4mm and OD 6mm made of quartz was used as the burner. Liquid n-heptane was delivered into a capillary from a syringe pump. Stable flames were established inside the burner with and without heat recirculating. Additionally, numerical simulations were conducted, and effects of equivalence ratio and external heat loss coefficient on diffusion flame were studied. Results show that, for a diffusion flame of liquid n-heptane in a small tube, as fuel flow rate increases, the flammable limits increase. The diffusion flame position moves downstream with increasing air flow, eventually stabilizing at the bottom of the outer tube until extinction. When the flame passes in the tube, the peak temperature would occur on the wall. If there is heat recirculating, the wall temperature of the inner tube is higher than the boiling point of liquid n-heptane. It is conducive to the pre-evaporation of liquid n-heptane. In contrast, if there is no heat recirculating, liquid fuel will be accumulated in the tube. The heat loss coefficient has a great influence on flammable limits of the tube burner without heat recirculating.